The Effect of Persuasive Messages in Promoting Home-Based Physical Activity During COVID-19 Pandemic - Carfora, Valentina; Catellani, Patrizia (Frontiers in Psychology, 2021)
We tested the plausibility of a persuasion model to understand the effects of messages framed in terms of gain, non-loss, non-gain, and loss, and related to the physical, mental and social consequences of doing physical activity at home during the lockdown restrictions. 272 Italian participants responded to a questionnaire on their attitude, intention, past behaviour and self-efficacy related to exercising at home. Then, participants were randomly assigned to four different message conditions: a) gain messages focused on the positive outcomes associated with doing physical activity at home; b) non-loss messages focused on the avoided negative outcomes associated with doing physical activity at home; c) non-gain messages focused on the missed positive outcomes associated with not doing physical activity at home; d) loss messages focused on the negative outcomes associated with not doing physical activity at home. After reading the messages, participants answered a series of questions regarding their perception of threat and fear, their evaluation of the messages, and again their attitude and intention towards exercising at home. Using multigroup structural equation modelling, we compared message conditions. Results showed that the perception of the messages as not threatening is the key point to activate a positive evaluation of the recommendation. The highest persuasive effect was observed in the case of the non-loss frame, which did not threaten the receivers, triggered a moderated fear and, in turn, activated a positive evaluation of the recommendation, higher attitude and intention to do home-based physical activity. Overall, these results advance our comprehension of the effects of message framing on receivers’ attitudes and intentions.